Answer:
The average rate of change is -18.
Explanation:
We are given the function:
![\displaystyle h(x) = -2x^2 - 2x](https://img.qammunity.org/2023/formulas/mathematics/college/aa4iyna2o4zo922uuxpxxrrrj1w0aymsvp.png)
And we want to find its average rate of change from x = 2 to x = 6.
Recall that to find the average rate of change between two points of any functions, we find the slope between the two endpoints. Hence, evaluate the endpoints:
![\displaystyle \begin{aligned} h(2) & = -2(2)^2 -2(2) \\ \\ & = -2(4)-4 \\ \\ & = -12\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/kt72sr5fj07jukp2g96o6fsup420q5s67c.png)
Likewise:
![\displaystyle \begin{aligned} h(6) &= -2(6)^2-2(6) \\ \\ & = -2(36) - 12 \\ \\ & = -84\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/wedmidtfkg5bglte2xvpfz2vrlrwjgso2d.png)
The slope between the two endpoints is therefore:
![\displaystyle \begin{aligned} (\Delta y)/(\Delta x) & = ((-84)- (-12))/((6)-(2)) \\ \\ & = (-72)/(4) \\ \\ & = -18\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/4ch5o2ismh446ebqvla22jb93i6aoopabo.png)
In conclusion, the average rate of change of h from x = 2 to x = 6 is -18.